IPO as an Exit startegy in Management Buyouts - Sheth, Vidhi Chetan (2008)
The basic subject to this research project is,IPO as an exit strategy in management buyouts. The paper provides with an understanding of the various characteristics and factors that have an impact on a buyout exit through an IPO. Discussions on the issues like the IPO versus other exit strategies, performance of a company's pre-IPO as well as post-IPO, the trends in the buyout and the IPO market, etc are done. For a better understanding and an in-depth knowledge about the topic, we have analyzed IPO exits that took place in three time periods; 1984-1989, 1993-1997 and 2004-2007. And further even six companies, two from each wave period have also been considered, which provides us with a gist of the characteristics, its success and its failure. Thus ANOVA and the case study approach are used to analyze both of the above mentioned aspects (the three wave periods and the six companies).